Efektivitas Pendekatan Student-Centered Learning dalam Pelatihan Survey Topografi di Bandung - Syafril Ramadhon (Jurnal Kewidyaiswaraan, 2020)
The aim of this study is to measure the effectiveness of using the Student-Centered Learning (SCL) approach in supporting the academic achievement of trainees in topographic survey training programs compared to the Teacher-Centered Learning (TCL) approach on aspects of knowledge and skill. The study was conducted quantitatively using a quasi-experiment method with a control group. The research sample is high school and vocational high school graduates in Bandung City and Bandung Regency with details of 20 people for the experimental group and 20 people for the control group. The study was conducted by comparing the learning outcomes of the experimental group and the control group on aspects of knowledge and skills. Data analysis was performed using descriptive statistics and t-test. The results showed that the implementation of the SCL approach was effective in improving the learning achievements of topographic survey training participants both in terms of knowledge and skills when compared to the TCL approach. The results of this study can be information for educators, especially Widyaiswara to strengthen their learning management competencies, so that training programs become more effective.